PELATIHAN STRATEGI CONTENT MARKETING PADA ANGGOTA KOPERASI DAN USAHA MIKRO KOTA SEMARANG - Pinem, Agusta; Christioko, Very; Gayuh, Victor (Join, 2021)
Content marketing is a modern marketing strategy where producers can plan, create and distribute specific content to advertise products. Content that can attract the right target audience, so as to attract potential buyers to become customers. However, the content marketing strategy needs to be understood more deeply first to be able to apply it by utilizing information technology, this is a problem for UKM. UKM still have minimal knowledge regarding content marketing strategies and social media applications for business. This training can provide an understanding to participants who are all UKM actors to be able to design marketing strategies by taking advantage of certain events and also utilizing information technology. Product packaging aesthetics can be made more attractive and can take advantage of social media as a marketing medium that can be reached by the wider community as potential buyers. Training is carried out directly by providing materials and training directly at the Lab of the Faculty of Information and Communication Technology. Increased understanding of the material was measured from a questionnaire given before and after the training.